2022
DOI: 10.1002/ls.1633
|View full text |Cite
|
Sign up to set email alerts
|

Impact of partial surface waviness on the tribological performance of hydrodynamic journal bearing

Abstract: In this paper, the static performance analysis of journal bearing having full and partial surface waviness has been presented. The surface waviness is to be considered in the full, first half, second half, and pressure-increasing and decreasing regions of the bearing for analysis. The effect of surface waviness is considered by modifying the lubricant flow governing Reynolds equation with the film thickness equation and it is solved with the finite element method to get performance parameters like bearing load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Now as per our recorded literature related to surface waviness, no study found related to the effect of partial surface waviness on journal bearing's dynamic and stability performance. The goal of the present work is to fill this gap and it is also an extension of the published work 24 which reported enhancement in the static performance of the journal bearing due to partial waviness in different regions of the bearing surface. In the present numerical study, the dynamic and stability performance of journal bearing with partial waviness in different regions, such as full, upper half, lower half, pressure rising and reducing region, as illustrated in Figure 3a,b, with different wave number and wave amplitudes have been evaluated at an average eccentricity ratio of 0.6.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Now as per our recorded literature related to surface waviness, no study found related to the effect of partial surface waviness on journal bearing's dynamic and stability performance. The goal of the present work is to fill this gap and it is also an extension of the published work 24 which reported enhancement in the static performance of the journal bearing due to partial waviness in different regions of the bearing surface. In the present numerical study, the dynamic and stability performance of journal bearing with partial waviness in different regions, such as full, upper half, lower half, pressure rising and reducing region, as illustrated in Figure 3a,b, with different wave number and wave amplitudes have been evaluated at an average eccentricity ratio of 0.6.…”
Section: Introductionmentioning
confidence: 95%
“…Yang et al 22 observed the dynamic behaviour of the wave bearing using the finite difference method and Reynolds equation and revealed that waviness influences the bearing stability. Bangotra and Sharma 23,24 reported that the surface waviness and the use of lubricant additives and the partial surface waviness enhance the static performance of journal bearings.…”
Section: Introductionmentioning
confidence: 99%
“…It was discovered that irregularities increase the value of minimum fluid film thickness and lubricant flow. Bangotra and Sharma 11,12 reported that due to the surface waviness, the load capacity increases, and the COF reduction and surface waviness in the pressure region is more effective in the circumferential direction than the axial direction.…”
Section: Introductionmentioning
confidence: 99%